CHOROIDAL VASCULARITY INDEX IN YOUNG CHOROIDEREMIA PATIENTS. Issue 5 (May 2021) - Murro, Vittoria; Mucciolo, Dario Pasquale; Giorgio, Dario; Passerini, Ilaria; Cipollini, Francesca; Virgili, Gianni; Giansanti, Fabrizio; Sodi, Andrea
Abstract : Purpose: To evaluate choroidal features in young patients affected by choroideremia (CHM). Methods: Young CHM patients and control subjects were recruited at the Eye Clinic in Florence. High-resolution choroidal imaging was obtained using swept-source optical coherence tomography with long optical coherence tomography scans (12 × 9 mm optical coherence tomography scans). We considered the subfoveal choroidal area within 9 mm of the optic disk in the horizontal plane and the subfoveal choroidal area within a 3-mm diameter centered over the fovea. The subfoveal choroidal thickness, total choroidal area, luminal area, stromal area, and choroidal vascularity index were assessed using the "ImageJ" software in both groups. Results: Eight patients (16 eyes; mean age, 19.3 ± 5.2 years) and seven control subjects (14 eyes; mean age, 19.0 ± 5.0 years) were included in this study. Best-corrected visual acuity was 20/20 in both eyes of seven CHM patients and in all control subjects and 20/25 in both eyes in one CHM patient. Mean subfoveal choroidal thickness did not differ between CHM patients and control subjects. Luminal area9mm, stromal area9mm, and total choroidal area9mm were reduced in patients compared with the control group. Luminal area3mm, stromal area3mm, and total choroidal area3mm did not differ between patients and control subjects. Choroidal vascularity index9mm and choroidal vascularity index3mm were not different between patients and control subjects. Conclusion: There are no differences in the choroidal vascularity index between young CHM patients and control subjects; this result suggests a simultaneous, proportional impairment of both the stromal and vascular components of the choroid in the early stages of the disease. Abstract : There are no differences in the choroidal vascularity index between young choroideremia patients and control subjects. This result suggests a simultaneous, proportional impairment of both the stromal and vascular components of the choroid in the early stages of the disease. This is the first work that studies choroidal vascularity index in choroideremia.